PEMBINAAN USAHA MIKRO KECIL MENENGAH (UMKM) OLEH PEMERINTAH KOTA PEKANBARU MASA PANDEMI COVID-19 2020-2022 - Zikri, Muhammad Al (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
The Covid-19 pandemic has had a significant impact on micro, small, and medium enterprises (MSMEs) in Pekanbaru City. According to a survey conducted by the Department of Cooperatives and MSMEs of Pekanbaru City, 50% of the 14,000 MSMEs in the city were negatively affected from 2020 to 2021. This research aims to reveal the roles and challenges faced by the Department of Cooperatives and MSMEs in the development of MSMEs during the Covid-19 pandemic. Using a qualitative method with a descriptive approach, this study describes the situation and challenges faced by MSMEs in Pekanbaru. Primary data were obtained from official documents and reports of the Department of Cooperatives and MSMEs of Pekanbaru City, as well as through direct field observations. This research identifies various problems faced by MSME players during the pandemic, such as a decline in revenue, difficulty accessing capital, and limited market reach. In response, central and local governments launched several assistance programs, including the MSME Funding Program, Partnership Cooperation Program, E-business & E-commerce Program, and Workshop and Training Program. This study provides important insights into how local governments play a role in supporting MSMEs during a crisis and the challenges that must be overcome to ensure the sustainability of small and medium-sized enterprises in emergency situations. The Department of Cooperatives and MSMEs of Pekanbaru City acts as a regulator, facilitator, and catalyst to support the implementation of these programs. However, during the 2020-2021 period, the implementation of several development and empowerment programs was hampered by the Large-Scale Social Restrictions (PSBB) policy. Nonetheless, development activities continued through data collection, partnerships (cooperation and capital assistance), facility licensing, institutional strengthening, and coordination with various stakeholders. Keywords: Department of Cooperatives and MSMEs of Pekanbaru City, Covid-19 Pandemic, MSME Development, Government Role.